Muscle tuning and preferred movement path: do we need a paradigm shift or should we redefine the old? - comment on Nigg et al. - Benedicte Vanwanseele; Xianyi Zhang; Kurt Schütte (Bern Open Publishing, 2018)
n the feature paper "Muscle tuning and preferred movement path - a paradigm shift", Benno Nigg and colleagues discuss that the impact and pronation paradigm should be abandoned as there is not enough biomechanical and epidemiological evidence supporting these paradigms. We agree that the paradigms, as defined in the paper, are currently not supported by strong scientific evidence however we argue that the lack of evidence originates from shortcomings in the methodological approach to these paradigms. In our commentary, we argue for a redefinition of the paradigms rather than defining two 'new' paradigms. A better methodological approach and definitions of the paradigms based on the current evidence are needed rather than to abandon them.